Use of the word “evolution” in the time of a global pandemic - Boyd, Sada M.; Freimuth, Sara; Xue, Carolyn; Lyons, Brandon; Nagori, Sana; Yu, Michael; Lozano-Huntelman, Natalie; Diamant, Eleanor S.; Yeh, Pamela J. (Frontiers in Communication, 2024)
The media can play a vital role in determining to what extent the general public understands scientific concepts. The understanding and acceptance of evolution are often influenced by factors beyond scientific knowledge alone, including education, politics, and media consumption habits. Although discussion of the COVID-19 pandemic and evolution had fixed itself in public discourse on many fronts, the media often avoided the usage of the word "evolve" and showed a preference for alternatives such as "emerge" or "mutate". We conducted a systematic analysis to gauge the prominence of the concept of evolution in media discussions across seven English-speaking countries. This involved assessing the frequency of the term "evolve" concerning viral evolution within newspaper articles using electronic databases. Of the 4,951 newspaper articles examined in this study, 11% discussed viral evolution. Out of those articles, 12% explicitly used the word "evolve". We found that countries did not significantly differ in their "evolve" usage, which may reflect similarities in views about COVID-19 and its evolution across countries or reliance on shared information sources when reporting on COVID-19. We also found that, as the pandemic progressed, the discussion on viral evolution as a topic had increased, but the frequency with which the word "evolve" was explicitly used had decreased. The COVID-19 pandemic has had a substantial impact on science and health news reporting. Although evolution plays a crucial role in the progression of the COVID-19 pandemic, the term "evolve" is not frequently highlighted in COVID-19 news coverage. Our research underscores the significant implications of language choice when describing evolutionary events, particularly in shaping the public's understanding of evolution, both in general and in the context of pandemics and infectious diseases.